Effect of Abaya Designs and Daily Wear Clothing on Thermal Comfort Measured with a Female Thermal Manikin (Journal of Fiber Bioengineering and Informatics, 2014)
Multiple layers of clothing are known to increase thermal resistance and evaporative resistance. Thisstudy investigates the effect of wearing abaya, an Islamic outerwear stipulated for women, on thermalresistance performance assessed with a female thermal manikin. Tests were conducted at two climaticconditions. The first set was at 23 ° C and 50% RH as the dry condition and the second set was at35 °C and 40% RH as the wet condition. Thermal resistance and evaporative resistance properties weremeasured by dressing a female thermal manikin in various ensembles of clothing within different typesof abaya. The test results revealed that for all abaya combinations with daily wear, the manikin neededless heat to maintain the average skin temperature than with daily wear clothing alone. This studysuggests that the abaya provided additional thermal and vapour resistance. Among the types of abayaevaluated, those worn on the head offered higher thermal resistance than those worn from the shoulderwith tight sleeves. Marginal variations were also observed on the basis of the clothing worn under theabaya.
Keywords: Abaya Design; Thermal Resistance; Evaporative Resistance; Thermal Manikin; Clothing Comfort